2021
DOI: 10.1155/2021/4558279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Cognitive and Exercise Interventions on Poststroke Cognitive Function: A Systematic Review and Meta-Analysis

Abstract: Objective. We investigated combined cognitive and exercise interventions in the literature and summarized their effectiveness in improving poststroke cognitive impairment (PSCI). Data Sources. Electronic databases and trial registries were searched from their inception until July 2020. Study Selection. Trials were collected with the following study inclusion criteria: (1) patients over 18 years of age who were diagnosed with PSCI; (2) combined cognitive-exercise interventions, regardless of the order of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…CEDT training is an innovative rehabilitation method that has been developed in recent years and has been proven effective in improving cognitive impairment, such as aging‐related cognitive impairment, post‐stroke cognitive impairment, and AD (Ali et al., 2022; Cui et al., 2023; Gavelin et al., 2020; Huber et al., 2022; Li et al., 2022). In our previous study, it was identified that CEDT training can directly improve cognitive impairment in CCI patients (Sun et al., 2021). In our current study, we analyzed the impacts and possible underlying mechanisms of exercise, cognitive, and CEDT interventions using an in vivo CCI model, in vitro OGD model in which the astrocytes and neuronal cells were co‐cultured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CEDT training is an innovative rehabilitation method that has been developed in recent years and has been proven effective in improving cognitive impairment, such as aging‐related cognitive impairment, post‐stroke cognitive impairment, and AD (Ali et al., 2022; Cui et al., 2023; Gavelin et al., 2020; Huber et al., 2022; Li et al., 2022). In our previous study, it was identified that CEDT training can directly improve cognitive impairment in CCI patients (Sun et al., 2021). In our current study, we analyzed the impacts and possible underlying mechanisms of exercise, cognitive, and CEDT interventions using an in vivo CCI model, in vitro OGD model in which the astrocytes and neuronal cells were co‐cultured.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have demonstrated that cognitive or exercise intervention is an effective method to improve cognitive impairment in stroke (Best et al., 2018; Michel & Mateer, 2006; Mura et al., 2018; Swatridge et al., 2017). The cognitive‐exercise dual‐task (CEDT) training, which combined cognitive training with exercise training, had a significant effect on the improvement of post‐stroke cognitive impairment in the clinical trials (He et al., 2018; Pang et al., 2018; Sun et al., 2021; Yeh et al., 2017). However, it is not clear whether CEDT training is more effective than single exercise or cognitive training, and what the underlying mechanisms are.…”
Section: Introductionmentioning
confidence: 99%
“…This sample size supports a 20% tracking loss rate. We established a minimum effect size of 0.75 standard deviations by considering the results of meta-analyses studying the effects of mindfulness or PE on cognition or emotional wellbeing in stroke patients (e.g., Abbott et al, 2014 ; Oberlin et al, 2017 ; Ali et al, 2021 ; Sun et al, 2021 ). The effect sizes reported in these papers range from small-moderate (between d = 0.30 and d = 0.50) to moderate-large (between d = 0.50 and d = 1), depending on the intervention and the outcome studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although very few studies had shown improvement in working memory [ 15 ], many studies had contradicting results to support this statement [ 1 , 2 ]. Some studies have shown improvement when combined cognitive and exercise interventions are included [ 22 ]. Because of the small sample size and other contradicting studies, further extensive sample studies are needed.…”
Section: Reviewmentioning
confidence: 99%